A new genus for the Blue-and-yellow Tanager (Aves: Passeriformes): a suggested adjustment to the classification of the Thraupidae - Piacentini, Vítor De Q. (Zootaxa, 2017)
Recent DNA-based studies have found that the genus Thraupis, as traditionally defined, is polyphyletic, with the Blue-and-yellow Tanager (historically treated as Thraupis bonariensis) being sister to the Fawn-breasted Tanager (Pipraeidea melanonota). As a result, most subsequent classifications lumped both species under a single genus, Pipraeidea. Here I show that both species differ markedly in plumage, morphology, voice, and behavior, each of them being more similar to a distantly related species than to each other. As such, I argue that the treatment of the Blue-and-yellow Tanager in Pipraeidea creates an undiagnosable genus contrasting greatly with the generic limits commonly applied to the tanagers. To avoid this situation, I propose the recognition of a new genus, Remsenornis gen. nov., for the Blue-and-yellow Tanager.